Targeting the Stroma in the Management of Pancreatic Cancer - Edwards, Penelope; Kang, Byung Woog; Chau, Ian (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) presents extremely aggressive tumours and is associated with poor survival. This is attributed to the unique features of the tumour microenvironment (TME), which is known to create a dense stromal formation and poorly immunogenic condition. In particular, the TME of PC, including the stromal cells and extracellular matrix, plays an essential role in the progression and chemo-resistance of PC. Consequently, several promising agents that target key components of the stroma have already been developed and are currently in multiple stages of clinical trials. Therefore, the authors review the latest available evidence on novel stroma-targeting approaches, highlighting the potential impact of the stroma as a key component of the TME in PC.